PERBEDAAN RERATA LIMFOSIT CD4 PADA PENDERITA HIV DENGAN DAN TANPA GANGGUAN MEMORI VERBAL - Ketut Widyastuti,* Ni Made Susilawathi,** I Made Susila Utama,*** Anak Agung Ayu Putri Laksmidewi** (NEURONA, 2017)
INTRODUCTION NEUROCOGNITIVE COMPLICATIONS IN HUMAN IMMUNODEFICIENCY VIRUS HIV PATIENTS ARE APPROXIMATELY51 WITH THE MOST COGNITIVE DOMAINS IMPAIRED IS MEMORY 63 VERBAL MEMORY IMPAIRMENT IN PATIENTS WITH HIV IS STILL FOUND ACTIVE ANTIRETROVIRAL THERAPY ARV THAT IT CAN INCREASE THE LEVELS OF LYMPHOCYTES CLUSTER OF DIFFERENTIATION 4 CD4 HAS WIDELY USED IMMUNE SUPPRESSION SHOWN IN CD4 LEVEL IS A STRONG DETERMINANT FOR COGNITIVE IMPAIRMENT